The characteristic and potential of green trade between China and regional comprehensive economic partnership countries - Xu, Yujie; Liao, Xianchun; Li, Meicun (Frontiers in Environmental Science, 2023)
This paper analyze the characteristics of green trade between China and Regional Comprehensive Economic Partnership (RCEP) countries from 2001 to 2020, and then adopts a stochastic frontier gravity (SFG) model and trade inefficiency (TIE) model to analyze the trade potential and the influencing factors of green trade between China and RCEP countries. The main conclusions are as follows: the green trade value continues to grow, with Japan and South Korea as the main green trade partners. The competitive advantage of Chinese green products and the complementarity of RCEP countries towards Chinese green products are both increasing. Per capita GDP, population of RCEP countries promote the green trade, while the geographical distance hinders green trade. In the item of TIE, governance ability and economic freedom promote the efficiency of green trade, while differences in environmental regulation and tariff rate hinders trade efficiency. At present, China has significant green trade potential with RCEP countries. The efficiency of green trade between China and Japan, South Korea, Singapore, Vietnam, and Australia is relatively low. China should actively tap into the demand for green trade and further develop the potential of green trade.